Brain ACE2 activation following brain aminopeptidase A blockade by firibastat in salt-dependent hypertension. Issue 6 (26th March 2021) - Hmazzou, Reda; Marc, Yannick; Flahault, Adrien; Gerbier, Romain; De Mota, Nadia; Llorens-Cortes, Catherine
Abstract: In the brain, aminopeptidase A (APA), a membrane-bound zinc metalloprotease, generates angiotensin III from angiotensin II. Brain angiotensin III exerts a tonic stimulatory effect on the control of blood pressure (BP) in hypertensive rats and increases vasopressin release. Blocking brain angiotensin III formation by the APA inhibitor prodrug RB150/firibastat normalizes arterial BP in hypertensive deoxycorticosterone acetate (DOCA)-salt rats without inducing angiotensin II accumulation. We therefore hypothesized that another metabolic pathway of brain angiotensin II, such as the conversion of angiotensin II into angiotensin 1-7 (Ang 1-7) by angiotensin-converting enzyme 2 (ACE2) might be activated following brain APA inhibition. We found that the intracerebroventricular (icv) administration of RB150/firibastat in conscious DOCA-salt rats both inhibited brain APA activity and induced an increase in brain ACE2 activity. Then, we showed that the decreases in BP and vasopressin release resulting from brain APA inhibition with RB150/firibastat were reduced if ACE2 was concomitantly inhibited by MLN4760, a potent ACE2 inhibitor, or if the Mas receptor (MasR) was blocked by A779, a MasR antagonist. Our findings suggest that in the brain, the increase in ACE2 activity resulting from APA inhibition by RB150/firibastat treatment, subsequently increasing Ang 1-7 and activating the MasR while blocking angiotensin III formation, contributes to the antihypertensive effect and the decrease in vasopressin release induced by RB150/firibastat. RB150/firibastat treatment constitutes an interesting therapeutic approach to improve BP control in hypertensive patients by inducing in the brain renin–angiotensin system, hyperactivity of the beneficial ACE2/Ang 1-7/MasR axis while decreasing that of the deleterious APA/Ang II/Ang III/ATI receptor axis.